Assessing vigilance in caregivers after traumatic brain injury: TBI-CareQOL Caregiver Vigilance. - Carlozzi, Noelle E.; Lange, Rael T.; Kallen, Michael A.; Boileau, Nicholas R.; Sander, Angelle M.; Massengale, Jill P.; Nakase-Richardson, Risa; Tulsky, David S.; French, Louis M.; Hahn, Elizabeth A.; Ianni, Phillip A.; Miner, Jennifer A.; et al. (Rehabilitation Psychology, 2020)
Objective: Caregivers of individuals with traumatic brain injury (TBI) frequently experience anxiety related to the caregiver role. Often this is due to a caregiver's perceived need to avoid people and situations that might upset or "trigger" the care recipient. There are currently no self-report measures that capture these feelings; thus, this article describes the development and preliminary validation efforts for the TBI-Caregiver Quality of Life (CareQOL) Caregiver Vigilance item bank. Design: A sample of 532 caregivers of civilians (n = 218) or service members/veterans (SMVs; n = 314) with TBI completed 32 caregiver vigilance items, other measures of health-related quality of life (RAND-12, Patient-Reported Outcomes Measurement Information System [PROMIS] Depression, PROMIS Social Isolation, Caregiver Appraisal Scale), and the Mayo-Portland Adaptability Inventory-4. Results: The final item bank contains 18 items, as supported by exploratory and confirmatory factor analysis, item response theory graded response modeling (GRM), and differential item functioning investigations. Expert review and GRM calibration data informed the selection of a 6-item short form and programming of a computer adaptive test. Internal consistency reliability for the different administration formats were excellent (reliability coefficients = .90). Three-week test-retest stability was supported (i.e., r = .78). Correlations between vigilance and other self-report measures supported convergent and discriminant validity (0.01 = r = .69). Known-groups validity was also supported. Conclusions: The new TBI-CareQOL Caregiver Vigilance computer adaptive test and corresponding 6-item short form were developed using established rigorous measurement development standards, providing the first self-report measure to evaluate caregiver vigilance. This development work indicates that this measure exhibits strong psychometric properties.